ANALYSIS OF SHARIA FINANCING STRATEGY BASED ON CROWDFUNDING IN SMES - Sari, Lili Puspita; Rohim, Ade Nur; Priyatno, Prima Dwi; Rahmawati, Lina (Universitas Muhammadiyah Prof DR HAMKA, 2025)
Research aims: The purpose of this study is to analyze strategies for developing sharia-based crowdfunding to support halal MSMEs. It aims to highlight key aspects such as education, regulation, technological innovation, institutional collaboration, and the provision of sharia-compliant investments that contribute to the growth and sustainability of the halal business ecosystem. Design/Methodology/Approach: This study employs a descriptive qualitative method with interview techniques. Research findings: The findings indicate that strategies for developing sharia-based crowdfunding for MSMEs include enhancing education, establishing regulations, creating technology-based products, collaborating with other institutions, and providing investments that comply with sharia principles. Theoretical Contribution/Originality: This study provides a new perspective on the role of sharia-based crowdfunding in supporting the growth of the halal MSME sector. It contributes to the academic discourse by expanding the existing literature on the integration between the halal economy and Islamic fintech, emphasizing how innovative financial mechanisms aligned with sharia principles can enhance access to funding and promote sustainable development within the halal industry. Practitioners/Policy Implications: Highlights the importance of synergy among education, regulation, and technological innovation in strengthening the sharia-compliant financing ecosystem for MSMEs. Research Limitations/Implications: The study remains descriptive and limited to interview findings, suggesting the need for further research using quantitative or comparative approaches to test the effectiveness of the proposed strategies.